Trunk muscle activity among older and obese individuals during one-handed carrying. (July 2019) - Badawy, Mohamed; Schall, Mark C.; Zabala, Michael E.; Coker, Jordan; Davis, Gerard A.; Sesek, Richard F.; Gallagher, Sean
Abstract: Manual material handling (MMH) is associated with the development of work-related musculoskeletal disorders (MSDs). One-handed carrying is a particularly challenging form of MMH. Age and obesity have been increasing among the general and working populations in the United States and worldwide. While older and obese workers are more susceptible to MSDs in comparison to younger, healthy workers, the effects of one-handed carrying on trunk muscle activity among these populations have not been comprehensively studied. In this paper, we evaluate the effects of age and obesity on trunk muscle activity of six trunk muscle pairs during one-handed carrying of different loads. The results suggest that older and obese individuals do not exhibit considerably larger muscle activity than young and non-obese individuals while carrying a load of approximately 10 kg in one hand for relatively short distances. Accordingly, 10 kg appears to be an acceptable load to be occasionally carried in one hand by older and/or obese individuals from a muscle activity perspective. Highlights: One-handed carrying among older and obese individuals has not been adequately studied. The effects of one-handed carrying on trunk muscle activity was examined. Muscle activity was mainly driven by the effect of load magnitude. Differences were comparable among individuals in different age and/or BMI categories. 10 kg was identified as a potentially acceptable short distance load limit.